PREVALENCE OF THE PERCEPTION OF THE BODY SELF-IMAGE AND EATING DISORDERS OF ADOLESCENTS OF THE FEMALE SEX OF DIFFERENT CITIES OF THE RONDÔNDIA STATE (Fiep Bulletin - online, 2011)
In the modern society, the search for “an ideal” image, that it is imposed by the dictatorship of the fashion, has contributed for the dissatisfaction of the body self-image among adolescents. The objective of this study was to evaluate the prevalence of the dissatisfaction and distortion of the body self-image in adolescents classified as normal for the Index of Body Mass (IBM), deriving of different cities of the state of Rondônia. Became part of the sample, 231 young and adolescents of 12 the 20 years, of the feminine sex, classified as normal for IBM (OMS, 1995) deriving of cities Rondonienses: Jaru (JAR), Ouro Preto D'Oeste (OPO), Presidente Médici (PMD) and Ji-Paraná (JPA). To evaluate the distortion of the body self-image [BSQ was opted to the Body Shape Questionnaire] and the Eating Attitudes Test was used [EAT-26] to evaluate the presence of eating disorders. In order to evaluate the prevalence of the satisfaction with the body self-image, been verified the indirect perception of Index of Body Mass (IBM) of evaluated, for the difference of the IBM weight measured (current) for the appraisers and the declared one as ideal for the same ones was verified. All the young had been submitted the measures adopting the standardizations of the International Society for Advancement in Kinanthropometry, to obtaining of IBM. The analysis of the data was made in the program Excel 2000. The low prevalence the distortion of the body self-image, verified by analysis of BSQ+ in all the cities (JPA=45,5%;OPO=64%;PMD=23,1% and JAR=42,8%) it is related with the sef-perception of evaluated what fat very fat. That more than the half of the group of adolescents of all the cities, if considers inside of the level of normality how much to the self-perception of its physical form (JPA=65,7%;OPO=66%;PMD=76,9% and JAR=61,9%),  as evidenced for the classification of IBM (OMS, 1995), excluding the prevalence of distortion of the body self-image. Still, these if feel unsatisfied what its physical form, wishing slim. These findings are evidences prevalent between adolescents derived the cities next to the capital of the state (JAR>OPO>JIP>PMD), where the pressures social and of media by beauty are more evident.
Keywords: beauty; adolescents; media